JALUR KHUSUS (PLEA BARGAINING) DALAM HUKUM ACARA PIDANA - Rezky Abdi Fratama (Badamai Law Journal, 2021)
Apart from analyzing, this research aims to know whether the concept of Jalur Khusus (Plea Bargaining) in settlement of criminal cases matches the legality Principle. Moreover, the research aimed to analyze how the legal arrangement of Jalur Khusus (Plea Bargaining) is in criminal procedural law in future. The used research method is normative legal research that focuses on exploring whether the concept of Jalur Khusus (Plea Bargaining) in settlement of criminal cases matches the legality. The second focus is to explore how the legal arrangement of Jalur Khusus (Plea Bargaining) is in criminal procedural law for the future. This research uses the approach of legislation  (Statute Approach), primarily Law No. 8 of 1981 on the Criminal Procedure code, along with all its implementing regulations and other relevant legislation, conceptual approach (Conceptual Approach), especially about the special pathways  (Plea Bargaining), and comparative approach  (Comparative Approach) specifically the arrangement of plea bargaining in other countries such as the United States, Canada, United Kingdom, France, Georgia, Poland and Italy. The research results, namely the Jalur Khusus  (Plea Bargaining) concept in settlement of criminal cases, are not appropriate or contrary to the Legality Principle. The reason is the system of proof, and formal truth will be hindered. According to an article in 3 KUHAP, it is already explicitly mentioned that the judiciary is carried out in the way stipulated in the law a quo. The legal arrangement of the concept of "Jalur Khusus" in the Criminal Procedural Law for the future in accordance with the context of the criminal justice system in Indonesia. Also, following the Principle of simple justice quickly and lightly costs are clarifying the negotiating parties in a special line, things negotiated in a special line, adding regulation of stages in a special path, criminal acts that can use special channels, and the form of agreement and binding power in jalur khusus.